1981
DOI: 10.1210/jcem-53-5-1047
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Endocrine Findings in a 31-Year-Old 45,X/ 46,Xdel(Y)(ql2 Male*

Abstract: This report describes genetic, endocrine, and histological findings in a 31-yr-old 45,X/46,Xdel(Y)(q12) male with gynecomastia and azoospermia. A preponderance of 45,X cells was found in all tissues studied. Endocrine data suggested an abnormal Leydig cell-pituitary gonadotroph axis, although the basal testosterone level and the response to short term administration of hCG were normal. Testicular histology showed Leydig cell hyperplasia and seminiferous tubule atrophy. These findings are compared to 17 similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Among these cases, the aberrant Y chromosome was described as being isodicentric,33 38-41or a ring chromosome,31 32 44 45 or just lacking Yq,1 34-37 40 42 43 as in the two cases, IHG8 and IHG22, described in this study. Most of these previously described infertile males with 45,X mosaic karyotypes and a non-fluorescent Y rarely had a “pure sterility” phenotype, but usually manifested several somatic features, mostly short stature,35 36 42 43gynaecomastia,34 36-38 or genital ambiguity 4243 In our study, however, all three patients with a 45,X mosaic cell line had a pure sterility phenotype, which was the case even in those with a high proportion of 45,X (patients IHG8 and IHG22).…”
Section: Discussionmentioning
confidence: 99%
“…Among these cases, the aberrant Y chromosome was described as being isodicentric,33 38-41or a ring chromosome,31 32 44 45 or just lacking Yq,1 34-37 40 42 43 as in the two cases, IHG8 and IHG22, described in this study. Most of these previously described infertile males with 45,X mosaic karyotypes and a non-fluorescent Y rarely had a “pure sterility” phenotype, but usually manifested several somatic features, mostly short stature,35 36 42 43gynaecomastia,34 36-38 or genital ambiguity 4243 In our study, however, all three patients with a 45,X mosaic cell line had a pure sterility phenotype, which was the case even in those with a high proportion of 45,X (patients IHG8 and IHG22).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical prognosis in such cases depends primarily on which malignant cell elements are present. Our review of the literature revealed two cases with similar chromosomal abnormalities presenting with gynaecomastia in addition to one or more other presenting features (Interlandi et al 1981, Ponzio et al 1981. To the best of our knowledge our patient is the first reported with an isochromosome of the Y in whom gynaecomastia was the sole presenting feature.…”
Section: Discussionmentioning
confidence: 58%
“…86 Numerous reports of men with similar deletions of distal Yq11 and azoospermia are in the literature. [86][87][88][89][90][91][92][93][94] Several azoospermic men with ring Y chromosomes [46,X,r(Y) and 45,X/46,X,r(Y)] also have been reported. 88 Sertoli Cell Only syndrome is a frequent histopathologic diagnosis in azoospermic men with absence of the distal Yq11 region.…”
Section: The Y Chromosome In Spermatogenesismentioning
confidence: 99%
“…Six of nine azoospermic men with cytogenetic deletions of the distal Yqll-Yql2 region and three of five azoospermic men with r(Y) had histopathologic diagnoses of germ cell aplasia; the remainder had presumptive evidence of this diagnosis. 86,87,[89][90][91][92]94 Analogous to the human, sterile XO,Sxr' male mice with absence of H-Y antigen expression determinants Hya and presumptive absence of the murine spermatogenesis gene Spy have histopathologic findings in their testes consistent with Sertoli Cell Only syndrome. 81 Recent molecular studies support the concept that sequences necessary for spermatogenesis are present on distal Yq11 and that deletion of some or all of the sequences can result in extreme conditions such as Sertoli Cell Only syndrome.…”
Section: The Y Chromosome In Spermatogenesismentioning
confidence: 99%